Physio Biochemical Aspects of Sleeping Patterns in Relation to Plasma Glycated Haemoglobin Level in Type 2 Diabetic Patients - Iram Qamar, Nadeem Abbas, Noor-Ul-Ain, Hassan Jamil, Jawad Hussain Qamber, Shazia Awan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Diabetes mellitus is a persistent metabolic condition distinguished by raised levels of glucose in the bloodstream, commonly referred to as hyperglycemia. This phenomenon arises due to insufficient endogenous insulin production or impaired insulin utilization by the body. Insulin is a hormone that is biosynthesized and secreted by the pancreatic gland, functioning to modulate the concentration of blood glucose in the body. Glycated hemoglobin, typically referred to as hemoglobin A1c or HbA1c, is a variant of hemoglobin that undergoes glycation upon prolonged exposure to elevated levels of glucose within the bloodstream. Hemoglobin is a crucial protein that is present within erythrocytes and is primarily responsible for the transportation of oxygen across the various tissues of the body. The assessment of HbA1c serves as a means of determining an individual's mean blood glucose levels during the preceding two to three months. The monitoring of long-term glycemic control in individuals with diabetes mellitus is widely recognized to be of utmost importance, with a valuable marker for this purpose being deemed necessary. The levels of HbA1c are commonly reported as a proportion of the total hemoglobin within the circulating blood in the form of a percentage. Objective: To compare the effects of sleeping patterns and plasma glycated haemoglobin levels in type 2 diabetic and non diabetic patients Study Design: Quantitative cross sectional Settings: Punjab Rangers Teaching Hospital, Lahore Duration: Four months i.e. 1st August 2022 to 31st December 2022 Data Collection Procedure: A pre validated questionnaire was used. Study was carried out at Punjab Rangers Teaching Hospital, Lahore. The total numbers of faculty members were 70 who participated after taking the informed consent. The study was done by simple random sampling technique. A fasting blood glucose analysis was conducted on all subjects through the collection of a 5cc blood sample. The study enrolled participants who were divided into two distinct groups based on their fasting blood glucose levels in which 35 were diabetic and 35 were controlled. Mean & standard deviation was calculated. P value is <0.005 means significant. Results: There were 70 participants in the study which equally divided into two groups i.e. thirty five each namely diabetic and controlled one. The participants in diabetic group include 18 males and 17 females while in control group 22 males and 13 females. After analyzing the data we came to know the statistical significant results were shown by insomnia severity index and HbA1c parameters as indicating major difference when compared both controlled and diabetic group in each parameter. Epworth sleepiness scale did not show any significant difference. Conclusion: It is concluded in this study that patients with poor diabetic control have less diabetic HbA1c control which increase higher levels of insomnia which clearly noted in the diabetic group when compared to control one. If we control the glycemic control of patients then definitely the level of insomnia decreases by providing the sleep comfort in daily life. Keywords: Diabetes mellitus, glycated haemoglobin, sleeping patterns, Type 2 diabetes, Insulin